Comparison of P2Y12 receptor inhibitors in patients with ST-elevation myocardial infarction in clinical practice: a propensity score analysis of five contemporary European registries. Issue 2 (22nd January 2020) - De Luca, Leonardo; Zeymer, Uwe; Claeys, Marc J; Dörler, Jakob; Erne, Paul; Matter, Christian M; Radovanovic, Dragana; Weidinger, Franz; Lüscher, Thomas F; Jukema, Johan Wouter; ,
Abstract: Aims: Among acute coronary syndromes (ACS), ST-segment elevation myocardial infarction (STEMI) has the most severe early clinical course. Recent randomized clinical trials have demonstrated that novel antithrombotic therapies improve in-hospital outcomes in STEMI patients. We aimed to describe the effectiveness and safety of P2 Y12 receptor inhibitors in clinical practice in patients with STEMI based on data from contemporary European ACS registries. Methods and results: Five registries from the PIRAEUS initiative (AAPCI/ADPAT, ALKK-PIC, AMIS Plus, Belgium STEMI, and EYESHOT) provided data for the assessment of P2 Y12 receptor inhibitor-based dual antiplatelet therapy. Registries were heterogeneous in terms of setting, patient characteristics, and treatment selection. Matched pair analysis and propensity score matching were used to assess all-cause in-hospital death rates based on data from 25 250 patients (8577 patients on prasugrel, 5995 on ticagrelor, and 10 678 on clopidogrel). The odds ratio (OR) for the death of any cause when compared with clopidogrel was 0.72 [95% confidence interval (CI) 0.62–0.84, P  < 0.001] in favour of the new P2 Y12 receptor inhibitors (prasugrel and ticagrelor combined). In the comparison between prasugrel and ticagrelor, there were no relevant differences (OR 0.97, 95% CI 0.77–1.23; P  = 0.81). Event rates of cardiovascular death and stroke were also substantially lower for the new P2 Y12 receptor inhibitors. The differences between clopidogrel and prasugrel or ticagrelor on major bleeding were numerically in the same order as for death of any cause but were not statistically significant. No differences in ischaemic and bleeding outcomes were observed between prasugrel and ticagrelor. Conclusion: This analysis suggests that the prasugrel or ticagrelor compared with clopidogrel have favourable outcomes in clinical practice while not being inferior in terms of safety.